Comprehensive analysis of the impact of iron and terbium co-dopant levels on the structural, thermal, and spectroscopic properties of hydroxyapatite - Kaygili, Omer; Duskun, Yusuf; Barzinjy, Azeez A.; Kareem, Rebaz Obaid; Ates, Tankut; Keser, Serhat; Ince, Turan (Elsevier Sci Ltd, 2025)
In recent years, there has been a growing interest in biomaterials for improving human living conditions. Hydroxyapatite (HAp), a biomaterial widely used in bone and teeth restoration, has been doped with iron (Fe) and terbium (Tb) to enhance its electronic properties and potential biomedical applications. Theoretical calculations revealed a decreasing trend in bandgap values with increasing concentrations of Fe and Tb, suggesting a shift from insulating to semiconducting behavior. The synthesized Fe and Tb doped HAp samples were characterized using X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, Raman spectroscopy, scanning electron microscopy (SEM), and thermogravimetric analysis (TGA). The results showed that the addition of Fe and Tb dopants led to changes in the lattice parameters, crystallinity, and morphology of HAp structure. The doped HAp samples exhibited improved thermal stability, and their FTIR and Raman spectra confirmed the presence of the phosphate group. SEM analysis revealed sphere-like nanoparticles and EDX results confirmed the presence of Fe and Tb in the doped samples. The (Ca + Tb + Fe)/P molar ratios were close to the ideal value of 1.667. The study demonstrates the potential of Fe and Tb-doped HAp as multifunctional materials in biomedicine and other fields requiring tunable electrical properties.
Keywords: Hydroxyapatite; Wet chemical method; Biomaterial; Terbium; Co-dopant